Development and Delivery of Species Distribution Models to Inform Decision-Making. (5th June 2019) - Sofaer, Helen R; Jarnevich, Catherine S; Pearse, Ian S; Smyth, Regan L; Auer, Stephanie; Cook, Gericke L; Edwards, Thomas C; Guala, Gerald F; Howard, Timothy G; Morisette, Jeffrey T; Hamilton, Healy
Abstract: Information on where species occur is an important component of conservation and management decisions, but knowledge of distributions is often coarse or incomplete. Species distribution models provide a tool for mapping habitat and can produce credible, defensible, and repeatable information with which to inform decisions. However, these models are sensitive to data inputs and methodological choices, making it important to assess the reliability and utility of model predictions. We provide a rubric that model developers can use to communicate a model's attributes and its appropriate uses. We emphasize the importance of tailoring model development and delivery to the species of interest and the intended use and the advantages of iterative modeling and validation. We highlight how species distribution models have been used to design surveys for new populations, inform spatial prioritization decisions for management actions, and support regulatory decision-making and compliance, tying these examples back to our model assessment rubric.